Period of latency, progression and duration of blockade of epidural anesthesia with lidocaine, bupivacaine or its association in dogs Período de latência, progressão e duração do bloqueio da anestesia epidural com lidocaína, bupivacaína ou sua associação em cães - Ronchi S.J.* (2019)
© 2019, Universidade Federal de Minas Gerais.The objective of this study was to evaluate the latency, duration of the effect, and cranial progression of lidocaine and bupivacaine alone or in combination, by epidural route in dogs, and measuring the average pressure of the epidural channel before and after the completion thereof. Eighteen dogs were allocated in three groups, which received epidural: lidocaine 2% (GL) 0.25ml / kg; bupivacaine 0.5% (GB) in the same volume, or the association of both (GLB) in a 1: 1 ratio. Heart and respiratory rates and systolic blood pressure (SBP) were evaluated before treatment (M0) and up to 60 minutes after epidural anesthesia. In addition, the pressure in the epidural canal was evaluated before and after the administration of the treatments, latency period, progression and duration of the block by interdigital and paravertebral pannicus clamping. There was a 12% decrease in SBP in the GL at all times and 16% at 30 minutes in GLB when compared to the baseline. The mean pressure in the epidural space before and after epidural anesthesia was-1.5 (±3.9) and 41 (±16) mmHg), 55% presented negative pressure in the epidural space. The latency period did not differ between groups (GL: 3.5±1.6; GB: 4.5±4.5; and GLB: 2.4±1 minutes) and the duration of blockade was higher in GB (GL: 125±24, GB: 176±24, and GLB: 153±35 minutes). The maximum progression of anesthetics was up to L1-T13 in GL, L4-L3 in GB and L3-L2 in GLB. It is concluded that the association of lidocaine with bupivacaine does not present advantages in relation to the use of the drugs isolated by the epidural route, with lidocaine progressing more cranially in relation to bupivacaine or the association. Lidocaine promoted the reduction of SBP, even when associated with bupivacaine, remaining within the reference values. Only 55% of the dogs presented negative mean pressure in the epidural space before administration of the drugs, so the drop test may not be efficient for locating the epidural space in all animals.